1996
DOI: 10.1175/1520-0434(1996)011<0506:llfosp>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lead Forecasts of Seasonal Precipitation in Africa Using CCA

Abstract: A potentially operational forecast system for 3-month total precipitation for three sections of the African continent has been developed at NOAA's Climate Prediction Center using the statistical method of canonical correlation analysis (CCA). The levels and sources of predictive skills have been explored at lead times of up to 1 year, using a cross-validation design. The predictor field is quasi-global sea surface temperature (SST). Four consecutive 3-month predictor periods are used to detect evolving as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 9 publications
(10 reference statements)
2
29
0
1
Order By: Relevance
“…Lamb, 1978a,b;Folland et al, 1986Folland et al, , 1991Lamb and Peppler, 1992;Hastenrath et al, 1995;Ward, 1998;Giannini et al, 2003). Furthermore, Barnston et al (1996) demonstrated that the time-space behaviour of the SST field alone influences the seasonal rainfall in certain regions/seasons for Africa, both on inter-annual and inter-decadal time-scales. For Ethiopia, Segele and Lamb (2005) examined the possible associations with ENSO and global SST for the onset, cessation, and growing length of the main rainy season (Kiremt).…”
Section: Variations In Global Sst Associated With June-september Ethimentioning
confidence: 97%
“…Lamb, 1978a,b;Folland et al, 1986Folland et al, , 1991Lamb and Peppler, 1992;Hastenrath et al, 1995;Ward, 1998;Giannini et al, 2003). Furthermore, Barnston et al (1996) demonstrated that the time-space behaviour of the SST field alone influences the seasonal rainfall in certain regions/seasons for Africa, both on inter-annual and inter-decadal time-scales. For Ethiopia, Segele and Lamb (2005) examined the possible associations with ENSO and global SST for the onset, cessation, and growing length of the main rainy season (Kiremt).…”
Section: Variations In Global Sst Associated With June-september Ethimentioning
confidence: 97%
“…This knowledge led to the development of objective operational seasonal forecasting systems for South Africa, but only as recently as the 1990s (e.g., Jury 1996;Jury et al 1999;Landman and Mason 1999;Mason 1998). Although the prediction problem over southern Africa was also addressed by modelers from outside the region (e.g., Barnston et al 1996), the South African-based institutions that started with prediction system development include the South African Weather Service (SAWS) and the Universities of the Witwatersrand, Pretoria, Cape Town, and Zululand. Although most of these efforts have initially been largely fragmented, the institutions in South Africa involved with the operational running of global circulation models started in 2003 to display their forecasts on the Global Forecasting Centre for Southern Africa web site (www.gfcsa.net).…”
Section: Introductionmentioning
confidence: 99%
“…The first one has been developed in season forecast [3,4]. So far, the experimental models for season forecast with different methods have been studied and developed [5][6][7][8][9]. Statistical method is a popular tool, divided into 3 main groups [10]: traditional statistical method; Statistical Downscaling (SD); Model Output Statistics (MOS).…”
Section: Introductionmentioning
confidence: 99%